A photovoltaic front side silver paste and a preparation method thereof

CN117766195BActive Publication Date: 2026-10-27CHANGZHOU JUHE NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311738176.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2026-10-27
Estimated Expiration
2043-12-18

AI Technical Summary

Technical Problem

[0003]但是,现在常规的光伏正面银浆料制备工艺在原料混合时多采用直接混合的方式,玻璃粉、银粉在一起分散时容易产生团聚现象导致浆料细度变大,这会影响浆料的印刷性,长期印刷的稳定性

Benefits of technology

本发明提供的光伏正面银浆料的制备方法中,将有机载体与玻璃粉进行预分散的过程,通过有机载体中的表面活性剂提前包覆玻璃粉,可以调节玻璃粉的表面活性,长链树脂可以给予玻璃粉分散的骨架,分散剂与长链树脂的共同作用,还能够避免玻璃粉体的团聚和沉降,上述预分散的过程总体上可以有助于提高玻璃粉表面和有机载体的润湿性,进而提高玻璃粉的分散性的同时,还能够优化最终得到的正面银浆料的细度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1789722070415-000001
    Figure REF-OBJ-1789722070415-000001
  • Figure REF-OBJ-1789722070415-000002
    Figure REF-OBJ-1789722070415-000002
  • Figure REF-OBJ-1789722070415-000003
    Figure REF-OBJ-1789722070415-000003
Patent Text Reader

Abstract

The application provides a preparation method of photovoltaic front silver paste, comprising the following steps: S1, preparing raw materials: the raw materials comprise 84.5-92 wt% of metal silver powder, 1.3-3.5 wt% of glass powder and 6-12 wt% of organic carrier; S2, pre-dispersing the mixture of the organic carrier and the glass powder to improve the wettability of the surface of the glass powder and the organic carrier; the pre-dispersing specifically comprises the following steps: mixing the organic carrier and the glass powder, centrifuging after defoaming, and dispersing the obtained slurry by a three-roll machine for at least two times, and the slurry needs to be rolled for at least two times each time; S3, mixing the metal silver powder and the slurry obtained after pre-dispersing in the step S2, and dispersing by a three-roll machine for at least two times, and the slurry needs to be rolled for at least two times each time. The wettability of the surface of the glass powder and the organic carrier is improved by pre-dispersing the mixture of the organic carrier and the glass powder, and then the fineness of the front silver paste is improved in the subsequent mixing and grinding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photovoltaic front-side silver paste technology, specifically to a photovoltaic front-side silver paste and its preparation method. Background Technology

[0002] In solar cells, screen printing is generally used to print the front electrode onto a silicon wafer, followed by drying and sintering to form a metal electrode. Screen printing is cost-effective, facilitating the industrialization and large-scale production of solar cells. Therefore, the front-side paste for solar cells must possess excellent screen printability, remaining stable during continuous and prolonged printing. Suitable front-side silver paste for screen printing typically consists of three parts: a conductive phase, an inorganic phase, and an organic phase. Silver powder and glass powder are uniformly dispersed in a carrier, which acts as a binder and provides suitable rheological properties. The dispersibility of silver and glass powder in the carrier can be assessed by the paste's fineness; the finer the fineness, the better the dispersibility. The dispersibility of the solar front-side paste affects its screen printability. Poorly dispersed pastes are prone to agglomeration, forming large particles that clog the screen and lead to poor printing. Therefore, optimizing the preparation method of solar front-side silver paste to achieve a finer paste fineness is crucial for its printability.

[0003] However, the conventional photovoltaic front-side silver paste preparation process often uses direct mixing when mixing raw materials. When glass powder and silver powder are dispersed together, agglomeration is likely to occur, resulting in a larger paste fineness. This will affect the printability of the paste and the stability of long-term printing. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide a photovoltaic front-side silver paste and its preparation method. By mixing and pre-dispersing organic carrier and glass powder, the wettability of the glass powder surface and organic carrier is improved, thereby increasing the fineness of the front-side silver paste during subsequent mixing and grinding, and further ensuring the improved printing performance and long-term printing stability of the front-side silver paste.

[0005] The first aspect of this invention provides a method for preparing a photovoltaic front-side silver paste, comprising the following steps: S1. Preparation of raw materials: The raw materials include 84.5~92 wt% silver powder, 1.3~3.5 wt% glass powder, and 6~12 wt% organic carrier; wherein, the organic carrier includes: 10~15 wt% resin, 4~7 wt% dispersant, 3~6 wt% thixotropic agent, 4~8 wt% surfactant, and the balance is solvent; S2. After mixing the organic carrier and glass powder, pre-dispersion is performed to improve the wettability of the glass powder surface and the organic carrier. The pre-dispersion specifically includes the following steps: mixing the organic carrier and glass powder, and after degassing and centrifugation, the resulting slurry is dispersed at least twice using a three-roll mill, and the slurry needs to be rolled at least twice for each dispersion. S3. After mixing the silver powder with the slurry obtained after pre-dispersion in step S2, disperse the mixture at least twice using a three-roll mill, and roll the slurry at least twice each time.

[0006] In one embodiment, the dispersant is at least one of dodecylamine, Nanben ED420 type dispersant, Nanben ED426 type dispersant, and oleamide.

[0007] In one embodiment, the thixotropic agent is at least one of polyamide wax, lithium stearate, polyhydroxystearic acid, and fumed silica.

[0008] In one embodiment, the surfactant is at least one of a silane coupling agent, polyethylene glycol, and Hypermer KD16 anionic surfactant.

[0009] In one embodiment, the solvent is at least one selected from dimethyl oxalate, ethylene glycol butyl ether benzoate, diethylene glycol butyl ether acetate, terpineol, tripropylene glycol methyl ether, dodecyl alcohol ester, diethylene glycol monobutyl ether, and glyceryl diacetate.

[0010] In one embodiment, in steps S2 and S3, the first dispersion inlet roller spacing of the three-roll mill is 120 μm, and the first dispersion outlet roller spacing is 60 μm; the second dispersion inlet roller spacing is 80 μm, and the second dispersion outlet roller spacing is 40 μm; the third dispersion inlet roller spacing is 40 μm, and the third dispersion outlet roller spacing is 20 μm; the fourth dispersion inlet roller spacing is 20 μm, and the fourth dispersion outlet roller spacing is 10 μm.

[0011] In one embodiment, in steps S2 and S3, the spindle speed of the three-roll mill is 200 rpm / min, the infeed pressure ranges from 2.90 to 3.10 N, and the outfeed pressure ranges from 2.90 to 3.10 N.

[0012] In one embodiment, in step S2, the degassing centrifugation speed is 400 r / min and the degassing centrifugation time is 120 s.

[0013] A second aspect of the present invention also provides a photovoltaic front-side silver paste, which is prepared by the above-described preparation method.

[0014] Compared with the prior art, the present invention has the following beneficial effects: In the preparation method of photovoltaic front-side silver paste provided by the present invention, the process of pre-dispersing the organic carrier and glass powder involves pre-coating the glass powder with surfactants in the organic carrier, which can adjust the surface activity of the glass powder. The long-chain resin can provide a framework for the dispersion of the glass powder. The combined effect of the dispersant and the long-chain resin can also prevent the agglomeration and sedimentation of the glass powder. The above pre-dispersion process can generally help improve the wettability of the glass powder surface and the organic carrier, thereby improving the dispersibility of the glass powder and optimizing the fineness of the final front-side silver paste. Detailed Implementation

[0015] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several changes and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0016] This invention provides a method for preparing a photovoltaic front-side silver paste, comprising: S1. Prepare raw materials: including 84.5~92 wt% silver powder, 1.3~3.5 wt% glass powder, and 6~12 wt% organic carrier; wherein, the organic carrier includes: 10~15 wt% resin, 4~7 wt% dispersant, 3~6 wt% thixotropic agent, 4~8 wt% surfactant, and the balance is solvent; S2. After mixing the organic carrier and glass powder, pre-dispersion is performed to improve the wettability of the glass powder surface and the organic carrier. The pre-dispersion specifically includes the following steps: mixing the organic carrier and glass powder, and after degassing and centrifugation, the resulting slurry is dispersed at least twice using a three-roll mill, and the slurry needs to be rolled at least twice each time. S3. After mixing the metallic silver powder with the slurry obtained after pre-dispersion in step S2, disperse it at least twice using a three-roll mill. Each dispersion requires rolling the slurry at least twice.

[0017] In the preparation method provided by the present invention, by pre-mixing and dispersing glass powder and organic carrier, the wettability of the glass powder surface and organic carrier can be improved, the dispersibility of glass powder can be improved, and the fineness of the prepared photovoltaic front silver paste can be optimized. Specifically, the surfactant in the organic carrier can pre-coat the glass powder to improve the surface activity of the glass powder, the long-chain resin can provide a skeleton for the dispersion of glass powder, and under the combined action of the long-chain resin and the dispersant, the agglomeration and sedimentation of the glass powder can be avoided during the three-roller dispersion process.

[0018] In some embodiments, the dispersant is at least one of dodecylamine, Nanben ED420 type dispersant, Nanben ED426 type dispersant, and oleamide.

[0019] In some embodiments, the thixotropic agent is at least one of polyamide wax, lithium stearate, polyhydroxystearic acid, and fumed silica.

[0020] In some embodiments, the surfactant is at least one of a silane coupling agent, polyethylene glycol, or Hypermer KD16 anionic surfactant.

[0021] In some embodiments, the solvent is at least one selected from dimethyl oxalate, ethylene glycol butyl ether benzoate, diethylene glycol butyl ether acetate, terpineol, tripropylene glycol methyl ether, dodecyl alcohol ester, diethylene glycol monobutyl ether, and glyceryl diacetate.

[0022] In one embodiment, in steps S2 and S3, the first dispersion roller spacing of the three-roll mill is 120 μm, and the first dispersion roller spacing is 60 μm; the second dispersion roller spacing is 80 μm, and the second dispersion roller spacing is 40 μm; the third dispersion roller spacing is 40 μm, and the third dispersion roller spacing is 20 μm; the fourth dispersion roller spacing is 20 μm, and the fourth dispersion roller spacing is 10 μm. The three-roll mill performs four dispersions in steps S2 and S3, and the roller spacing gradually decreases in each dispersion. This helps to gradually reduce the fineness of the paste during each three-roll dispersion process, so as to ensure that the final photovoltaic front-side silver paste reaches the required fineness.

[0023] In some embodiments, in steps S2 and S3, the spindle speed of the three-roll mill is 200 rpm / min, the infeed pressure range is 2.90~3.10N, and the outlet pressure range is 2.90~3.10N. If the spindle speed is too fast, unnecessary heat will be generated during the dispersion process, affecting the performance of the slurry. The infeed and outlet pressures also need to be within a suitable range. If the pressure is too high, it will affect the state of the metallic silver powder, resulting in the appearance of flake silver, which in turn affects the performance of the product.

[0024] In some embodiments, in step S2, the degassing centrifugation speed is 400 r / min and the degassing centrifugation time is 120 s.

[0025] Example 1

[0026] S1. Prepare raw materials: 84.5 wt% silver powder, 3.5 wt% glass powder, and 12 wt% organic carrier; wherein, the organic carrier includes 10 wt% resin, 7 wt% dispersant, 3 wt% thixotropic agent, 8 wt% surfactant, and 72 wt% solvent.

[0027] S2. The organic carrier and glass powder are mixed, and the resulting slurry after degassing and centrifugation is dispersed four times using a three-roll mill. Each dispersion requires rolling the slurry twice. The first dispersion roller spacing is 120μm, and the first dispersion roller spacing is 60μm; the second dispersion roller spacing is 80μm, and the second dispersion roller spacing is 40μm; the third dispersion roller spacing is 40μm, and the third dispersion roller spacing is 20μm; the fourth dispersion roller spacing is 20μm, and the fourth dispersion roller spacing is 10μm. The spindle speed of the three-roll mill is 200rpm / min, the roller inlet pressure range is 2.9N, the roller outlet pressure range is 2.9N, the degassing centrifugation speed is 400r / min, and the degassing centrifugation time is 120s.

[0028] S3. After mixing the metallic silver powder with the slurry obtained after pre-dispersion in step S2, the mixture is then dispersed four times using a three-roll mill. Each dispersion requires rolling the slurry twice. The roller spacing for the first dispersion is 120 μm, and the roller spacing for the first dispersion is 60 μm. The roller spacing for the second dispersion is 80 μm, and the roller spacing for the second dispersion is 40 μm. The roller spacing for the third dispersion is 40 μm, and the roller spacing for the third dispersion is 20 μm. The roller spacing for the fourth dispersion is 20 μm, and the roller spacing for the fourth dispersion is 10 μm. The spindle speed of the three-roll mill is 200 rpm / min, the roller pressure range is 2.9 N, the roller pressure range is 2.9 N, the centrifugation speed for degassing is 400 r / min, and the centrifugation time for degassing is 120 s.

[0029] The silver paste prepared by the above steps will be subjected to a fineness test as required by national standards. The test method is as follows: Under an environment with a temperature of 15℃~35℃, relative humidity of 45%~75%, and atmospheric pressure of 86 kPa~106 kPa, the fineness gauge is cleaned with a suitable chemically pure cleaning agent. The sample is placed evenly in the deepest part of the groove of the fineness gauge. The scraper is held with both hands in the deepest part of the groove, so that the scraper is perpendicular to the surface of the fineness gauge. The sample is scraped across the surface of the fineness gauge from the deepest part of the groove at a uniform speed, so that the sample fills the groove and no sample is left on the plate. The whole operation is completed within 3 seconds. Within 3 seconds, the scraped fineness gauge is held horizontally and tilted so that the line of sight is at an angle of 20°~30° with the plane of the groove. The sample is observed against the light to find the position where two longitudinal stripes first appear in the groove and the particle reading is recorded. The same operation method is used to measure no less than 5 samples.

[0030] The fineness test results of the front silver paste obtained in Example 1 are shown in Table 1: Table 1 Example 2

[0031] S1. Prepare raw materials: 92 wt% silver powder, 2 wt% glass powder, and 6 wt% organic carrier; wherein, the organic carrier includes 12 wt% resin, 5.5 wt% dispersant, 6 wt% thixotropic agent, 6 wt% surfactant, and 81.5 wt% solvent.

[0032] S2. The organic carrier and glass powder are mixed, and the resulting slurry after degassing and centrifugation is dispersed four times using a three-roll mill. Each dispersion requires rolling the slurry twice. The first dispersion roller spacing is 120μm, and the first dispersion roller spacing is 60μm; the second dispersion roller spacing is 80μm, and the second dispersion roller spacing is 40μm; the third dispersion roller spacing is 40μm, and the third dispersion roller spacing is 20μm; the fourth dispersion roller spacing is 20μm, and the fourth dispersion roller spacing is 10μm. The spindle speed of the three-roll mill is 200rpm / min, the roller inlet pressure range is 3N, the roller outlet pressure range is 3N, the degassing centrifugation speed is 400r / min, and the degassing centrifugation time is 120s.

[0033] S3. After mixing the metallic silver powder with the slurry obtained after pre-dispersion in step S2, the mixture is then dispersed four times using a three-roll mill. Each dispersion requires rolling the slurry twice. The roller spacing for the first dispersion is 120 μm and the roller spacing for the first dispersion is 60 μm; the roller spacing for the second dispersion is 80 μm and the roller spacing for the second dispersion is 40 μm; the roller spacing for the third dispersion is 40 μm and the roller spacing for the third dispersion is 20 μm; and the roller spacing for the fourth dispersion is 20 μm and the roller spacing for the fourth dispersion is 10 μm. The spindle speed of the three-roll mill is 200 rpm / min, the roller pressure range is 3 N, the roller pressure range is 3 N, the centrifugation speed for degassing is 400 r / min, and the centrifugation time for degassing is 120 s.

[0034] The front silver paste prepared by the above steps was subjected to a fineness test as required by national standards, and the test method was the same as that in Example 1.

[0035] The fineness test results of the front silver paste obtained in Example 2 are shown in Table 2: Table 2 Example 3

[0036] S1. Prepare raw materials: 89.7 wt% silver powder, 1.3 wt% glass powder, and 9 wt% organic carrier; wherein, the organic carrier includes 15 wt% resin, 4 wt% dispersant, 4 wt% thixotropic agent, 4 wt% surfactant, and 83 wt% solvent.

[0037] S2. The organic carrier and glass powder are mixed, and the resulting slurry after degassing and centrifugation is dispersed four times using a three-roll mill. Each dispersion requires rolling the slurry twice. The first dispersion roller spacing is 120μm, and the first dispersion roller spacing is 60μm; the second dispersion roller spacing is 80μm, and the second dispersion roller spacing is 40μm; the third dispersion roller spacing is 40μm, and the third dispersion roller spacing is 20μm; the fourth dispersion roller spacing is 20μm, and the fourth dispersion roller spacing is 10μm. The spindle speed of the three-roll mill is 200rpm / min, the roller inlet pressure range is 3.1N, the roller outlet pressure range is 3.1N, the degassing centrifugation speed is 400r / min, and the degassing centrifugation time is 120s.

[0038] S3. After mixing the metallic silver powder with the slurry obtained after pre-dispersion in step S2, the mixture is then dispersed four times using a three-roll mill. Each dispersion requires rolling the slurry twice. The roller spacing for the first dispersion is 120 μm, and the roller spacing for the first dispersion is 60 μm. The roller spacing for the second dispersion is 80 μm, and the roller spacing for the second dispersion is 40 μm. The roller spacing for the third dispersion is 40 μm, and the roller spacing for the third dispersion is 20 μm. The roller spacing for the fourth dispersion is 20 μm, and the roller spacing for the fourth dispersion is 10 μm. The spindle speed of the three-roll mill is 200 rpm / min, the roller pressure range is 3.1 N, the roller pressure range is 3.1 N, the centrifugation speed for degassing is 400 r / min, and the centrifugation time for degassing is 120 s.

[0039] The front silver paste prepared by the above steps was subjected to a fineness test as required by national standards, and the test method was the same as that in Example 1.

[0040] The fineness test results of the front silver paste obtained in Example 3 are shown in Table 3: Table 3 Comparative Example 1 S1. Prepare raw materials: 84.5 wt% silver powder, 3.5 wt% glass powder, and 12 wt% organic carrier; wherein the organic carrier includes 10 wt% resin, 7 wt% dispersant, 3 wt% thixotropic agent, 8 wt% surfactant, and 72 wt% solvent, which is the same as the raw material composition ratio in Example 1.

[0041] S2. After mixing all raw materials, disperse them four times using a three-roll mill. Each dispersion requires rolling the slurry twice. The first dispersion roller spacing is 120μm, and the first dispersion roller spacing is 60μm; the second dispersion roller spacing is 80μm, and the second dispersion roller spacing is 40μm; the third dispersion roller spacing is 40μm, and the third dispersion roller spacing is 20μm; the fourth dispersion roller spacing is 20μm, and the fourth dispersion roller spacing is 10μm. The spindle speed of the three-roll mill is 200rpm / min, the roller inlet pressure range is 2.9N, the roller outlet pressure range is 2.9N, the degassing centrifugation speed is 400r / min, and the degassing centrifugation time is 120s.

[0042] The front silver paste obtained from the above steps was subjected to a fineness test as required by national standards, using the same test method as in Example 1.

[0043] The fineness test results of the front silver paste obtained in Comparative Example 1 are shown in Table 4: Table 4 Comparative Example 2 S1. Prepare raw materials: 84.5 wt% silver powder, 3.5 wt% glass powder, and 12 wt% organic carrier; wherein the organic carrier includes 10 wt% resin, 7 wt% dispersant, 3 wt% thixotropic agent, 8 wt% surfactant, and 72 wt% solvent, which is the same as the raw material composition ratio in Example 1.

[0044] S2. After mixing all raw materials, disperse them five times using a three-roll mill. Each dispersion requires rolling the slurry twice. The first dispersion roller spacing is 120μm for the inlet roller and 60μm for the outlet roller; the second dispersion roller spacing is 80μm for the inlet roller and 40μm for the outlet roller; the third dispersion roller spacing is 40μm for the inlet roller and 20μm for the outlet roller; the fourth dispersion roller spacing is 20μm for the inlet roller and 10μm for the outlet roller; the fifth dispersion roller spacing is 12μm for the inlet roller and 6μm for the outlet roller. The spindle speed of the three-roll mill is 200rpm / min, the inlet roller pressure range is 3.2N, the outlet roller pressure range is 3.2N, the degassing centrifugation speed is 400r / min, and the degassing centrifugation time is 120s.

[0045] The front silver paste obtained from the above steps was subjected to a fineness test as required by national standards, using the same test method as in Example 1.

[0046] The fineness test results of the front silver paste obtained in Comparative Example 2 are shown in Table 5: Table 5 Comparing Tables 1 and 4, it can be seen that the fineness of the front silver paste in the comparative example prepared by conventional methods is much greater than that of the front silver paste in the examples. This proves that in the preparation method of photovoltaic front silver paste provided by the present invention, by pre-mixing and dispersing glass powder and organic carrier, the wettability of the glass powder surface and organic carrier can be improved, the dispersibility of glass powder can be improved, and the fineness of the prepared photovoltaic front silver paste can be optimized.

[0047] Comparing Tables 1 and 5, it can be seen that the fineness of the front silver paste in Comparative Example 2, which was prepared by increasing the rolling pressure and reducing the rolling gap, is much greater than that of the front silver paste in Example 1. This proves that in the preparation method of photovoltaic front silver paste provided by the present invention, by pre-mixing and dispersing the glass powder and the organic carrier, the wettability of the glass powder surface and the organic carrier can be improved, the dispersibility of the glass powder can be improved, and the fineness of the prepared photovoltaic front silver paste can be optimized.

[0048] Specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. Unless otherwise specified, the embodiments and features described in this application can be arbitrarily combined with each other.

Claims

1. A method for preparing a photovoltaic front-side silver paste, characterized in that, Includes the following steps: S1. Preparation of raw materials: The raw materials include 84.5~92 wt% silver powder, 1.3~3.5 wt% glass powder, and 6~12 wt% organic carrier; wherein, the organic carrier includes: 10~15 wt% resin, 4~7 wt% dispersant, 3~6 wt% thixotropic agent, 4~8 wt% surfactant, and the balance is solvent; S2. After mixing the organic carrier and glass powder, pre-dispersion is performed to improve the wettability of the glass powder surface and the organic carrier. The pre-dispersion specifically includes the following steps: mixing the organic carrier and glass powder, and after degassing and centrifugation, the resulting slurry is dispersed at least twice using a three-roll mill, and the slurry needs to be rolled at least twice for each dispersion. S3. After mixing the silver powder with the slurry obtained after pre-dispersion in step S2, disperse the mixture at least twice using a three-roll mill, with each dispersion requiring at least two passes through the rollers; and... In steps S2 and S3, the distance between the first dispersing roller and the first dispersing roller is 120 μm, and the distance between the first dispersing roller and the first dispersing roller is 60 μm; the distance between the second dispersing roller and the second dispersing roller is 80 μm, and the distance between the second dispersing roller and the second dispersing roller is 40 μm; the distance between the third dispersing roller and the third dispersing roller is 40 μm, and the distance between the third dispersing roller and the third dispersing roller is 20 μm; the distance between the fourth dispersing roller and the fourth dispersing roller is 20 μm, and the distance between the fourth dispersing roller and the fourth dispersing roller is 10 μm.

2. The method for preparing photovoltaic front-side silver paste according to claim 1, characterized in that, The dispersant is at least one of dodecylamine, Nanben ED420 dispersant, Nanben ED426 dispersant, and oleamide.

3. The method for preparing photovoltaic front-side silver paste according to claim 1, characterized in that, The thixotropic agent is at least one of polyamide wax, lithium stearate, polyhydroxystearic acid, and fumed silica.

4. The method for preparing photovoltaic front-side silver paste according to claim 1, characterized in that, The surfactant is at least one of silane coupling agent, polyethylene glycol, and Hypermer KD16 anionic surfactant.

5. The method for preparing photovoltaic front-side silver paste according to claim 1, characterized in that, The solvent is at least one of dimethyl oxalate, ethylene glycol butyl ether benzoate, diethylene glycol butyl ether acetate, terpineol, tripropylene glycol methyl ether, dodecyl alcohol ester, diethylene glycol monobutyl ether, and glyceryl diacetate.

6. The method for preparing photovoltaic front-side silver paste according to claim 5, characterized in that, In steps S2 and S3, the spindle speed of the three-roll mill is 200 rpm, the infeed pressure ranges from 2.90 to 3.10 N, and the outfeed pressure ranges from 2.90 to 3.10 N.

7. The method for preparing photovoltaic front-side silver paste according to claim 1, characterized in that, In step S2, the degassing centrifugation speed is 400 r / min, and the degassing centrifugation time is 120 s.

8. A photovoltaic front-side silver paste, characterized in that, Prepared by the preparation method described in any one of claims 1-7.

Citation Information

Patent Citations

  • Sliver electrode slurry for back electric field of silicon solar cell and preparation method thereof

    CN102354545A